Controlled preparation of thin fibrin films immobilized at solid surfaces - Riedel, Tomás; Brynda, Eduard; Dyr, Jan E; Houska, Milan (Journal of biomedical materials research. Part A, 2009)
A technique for coating surfaces with attached fibrin structures without the formation of fibrin gel in bulk solution was developed. It is based on the catalytic effect of the surface-bound thrombin on fibrinogen stabilized with inhibitor which inhibits thrombin in solution but not the thrombin on the surface. Such an inhibitor is antithrombin, the effect of which may be enhanced with heparin. Fibrinogen is first adsorbed on the substrate surface and then incubated with thrombin. The unbound thrombin is washed out and the surface is incubated with fibrinogen solution containing antithrombin III and heparin. A fibrin gel forms at the surface by the action of surface-bound thrombin on ambient fibrinogen solution; however, the gel formation in bulk solution catalyzed by thrombin partially released from the surface is suppressed. By utilizing antithrombin-independent inhibitors or repeating thrombin binding and incubation with fibrinogen solution, the amount of surface-attached fibrin gel can be controlled. The formation of immobilized fibrin networks was observed using surface plasmon resonance and turbidity measurements and morphology was observed by TEM, SEM, and AFM. Using this technique, a porous scaffold made of polylactide fibers was coated with fibrin without filling the space between fibers with a bulk fibrin gel. The technique makes it possible to coat the inner surface of porous scaffolds with surface-attached fibrin gel while preserving free volume for cell migration into the pores.
Keywords: poréznost; fibrinolytika; prasata; Swine; povrchové vlastnosti; hirudiny; Porosity; Protease Inhibitors; testování materiálů; Materials Testing; Methylmethacrylates; Fibrinolytic Agents; inhibitory proteas; trombin; methylmetakryláty; chloromethylketony aminokyselin; polyhydroxyethylmethakrylát; Animals; fibrin; lidé; biokompatibilní materiály; Thrombin; Humans; Polyhydroxyethyl Methacrylate; zvířata; Surface Properties; Tissue Scaffolds; Fibrin; fibrinogen; tkáňové podpůrné struktury; Fibrinogen; Amino Acid Chloromethyl Ketones; Biocompatible Materials; Hirudins